(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
This study is an attempt to shed light on the issue of translating English auxiliary verbs in declarative sentences into Arabic. It aims to identify the students’ problems in translating English auxiliary verbs into Arabic. In addition, it aims to examine the extent to which the translation courses taught at the faculty affect students’ translations. To achieve these aims, the researchers use a test of translation for data collection. The test includes 20 statements including auxiliary verbs. The sample is 40 English Foreign language (EFL) students at the Faculty of Arts, al-Asmariya Islamic University, Zliten. The results of this research show that the students committed different types of errors in translating English auxiliaries into Arabic such as wrong equivalents in translation and omitting the equivalence. Furthermore, the results of the study reveal that the percentage of the correct and acceptable translations of the group who have not studied any translation courses and the percentage of the other group who have studied one or more translation courses are approximately the same. In words, the translation courses do not affect the student’s proficiency in translation.